2014
DOI: 10.1002/stem.1611
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Chimeric Receptor CD4ζby Natural Killer Cells Derived from Human Pluripotent Stem Cells Improves In Vitro Activity but Does Not Enhance Suppression of HIV Infection In Vivo

Abstract: Cell-based immunotherapy has been gaining interest as an improved means to treat HIV/AIDS. Human embryonic stem cells (hESCs) and induced pluripotent stem cells (iPSCs) could become a potential resource. Our previous studies have shown hESC and iPSC-derived natural killer (NK) cells can inhibit HIV-infected targets in vitro. Here, we advance those studies by expressing a HIV chimeric receptor combining the extracellular portion of CD4 to the CD3ζ intracellular signaling chain. We hypothesized that expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
81
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 77 publications
1
81
0
1
Order By: Relevance
“…We found that the newly designed CAR-T cells, here referred to as VC-CAR-T cells, were able to induce T cell-mediated cytolysis after coculture with gp120-expressing cells and wild-type HIV-1-infected CD4 ϩ T cells. We also found that VC-CAR-T cells display superior potency compared to the CD4-CAR described previously (26,27,(31)(32)(33)(34)(35)(36). Importantly, we have also confirmed that they can effectively kill the reactivated HIV-1-infected CD4 ϩ T lymphocytes isolated from HIV-1-infected patients.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…We found that the newly designed CAR-T cells, here referred to as VC-CAR-T cells, were able to induce T cell-mediated cytolysis after coculture with gp120-expressing cells and wild-type HIV-1-infected CD4 ϩ T cells. We also found that VC-CAR-T cells display superior potency compared to the CD4-CAR described previously (26,27,(31)(32)(33)(34)(35)(36). Importantly, we have also confirmed that they can effectively kill the reactivated HIV-1-infected CD4 ϩ T lymphocytes isolated from HIV-1-infected patients.…”
supporting
confidence: 84%
“…Therefore, we chose to use VRC01-28BBZ-3-expressing T cells, here referred to as VC-CAR-T cells, for subsequent experiments. Previous studies have reported that CD4-based CAR-T cells, referred to here as CD4-CAR-T cells, display direct cytotoxic activity against HIV-1 Env-expressing target cells (26,27,(31)(32)(33)(34)(35)(36). To compare the efficiency of CD4-CAR and VC-CAR, we generated the former by replacing the VC-CAR scFv with the human CD4 extracellular domain and transduced this construct into CD8 ϩ T lymphocytes (Fig.…”
Section: Selection Of the Most Efficient Car Moiety To Identify The mentioning
confidence: 99%
See 1 more Smart Citation
“…Early clinical successes with CARs against leukemia and lymphoma (28,29) have garnered particular recognition (30), and the strategy has been proposed for use against viruses, including HIV (reviewed in references 31, 32, 33, and 34). Indeed, previous reports demonstrated favorable in vitro results with CARs targeted by single-chain variable-region antibody (Ab) constructs directed against the gp120 or gp41 subunits of HIV-1 Env (35)(36)(37)(38) as well as with CARs employing extracellular CD4 domains (35,36,(39)(40)(41)(42). Clinical studies were conducted more than a decade ago with CD4 CARs (43)(44)(45); see also https://clinicaltrials.gov/ct2/show/NCT01013415), and subsequent analyses of peripheral blood samples verified long-term persistence as well as retention of CAR expression and the proliferative potential of adoptively transferred CAR-transduced T cells (CAR-T) (46).…”
mentioning
confidence: 99%
“…Recently, Ni et al took a novel strategy to utilize the anti-HIV specificity of TCRξ by engineering it into hESCs/iPSCs. After differentiation to NK cells, these modified counterparts were effective in inhibiting HIV-1 replication in NSG mice 53 .…”
Section: Revolution In Gene Modification:-mentioning
confidence: 99%